Correlation between knowledge level and mother's motivation to do pap smear screening - Nuristy Brillian Ainindyahsari Winarna; Suratini Suratini; Luluk Rosida (Universitas 'Aisyiyah Yogyakarta, 2022)
The low level of Pap smear screening is influenced by low knowledge. The purpose of this study was to analyze the correlation between the level of knowledge and the mother's motivation to perform a pap smear examination. This research used the Correlational Analytical method with the Cross-Sectional approach. The study population was all women of childbearing age living in Kricak village, RW 06, Kricak, Tegalrejo, Yogyakarta, totaling 49 women. Samples were taken based on the total sampling technique. Data analysis was performed with Kendall's Tau. The results revealed that as many as 12.2% of women of childbearing age (WUS) had good knowledge, 26.5% had sufficient knowledge and 61.2% had poor knowledge. In terms of motivation, as many as 28 respondents (57.1%) or most of the sample, have motivation in the category of poor with poor knowledge. The significance value obtained was 0.001 with a correlation value of 0.591. This finding suggests that there is a correlation between knowledge and a mother's motivation to perform a Pap smear screening where the correlation is in the medium range of closeness. The Tegalrejo Yogyakarta Health Center is expected to educate people about the dangers of cervical cancer and the importance of getting a pap smear exam.